Facial mask acute effects on affective/psychological and exercise performance responses during exercise: A meta-analytical review - Glänzel, Marcelo Henrique; Barbosa, Igor Martins; Machado, Esthevan; Prusch, Samuel Klippel; Barbosa, Ariadine Rodrigues; Lemos, Luiz Fernando Cuozzo; Schuch, Felipe Barreto; Lanferdini, Fábio Juner (Frontiers in Physiology, 2022)
Background: Face masks are widely used during the COVID-19 pandemic as one of the protective measures against the viral infection risk. Some evidence suggests that face mask prolonged use can be uncomfortable, and discomfort can be exacerbated during exercise. However, the acute responses of mask-wearing during exercise on affective/psychological and exercise performance responses is still a topic of debate. Purpose: To perform a systematic review with meta-analysis of the acute effects of mask-wearing during exercise on affective/psychological and exercise performance responses in healthy adults of different/diverse training status. Methods: This review (CRD42021249569) was performed according to Cochrane’s recommendations, with searches performed in electronic (PubMed, Web of Science, Embase, SportDiscus, and PsychInfo) and pre-print databases (MedRxiv, SportRxiv, PsyArXiv, and Preprint.Org). Syntheses of included studies’ data were performed, and the RoB-2 tool was used to assess the studies’ methodological quality. Assessed outcomes were affective/psychological (discomfort, stress and affective responses, fatigue, anxiety, dyspnea, and perceived exertion) and exercise performance [time-to-exhaustion (TTE), maximal power output (POMAX), and muscle force production] parameters. Available data were pooled through meta-analyses. Results: Initially 4587 studies were identified, 36 clinical trials (all crossover designs) were included. A total of 749 (39% women) healthy adults were evaluated across all studies. The face mask types found were clothing (CM), surgical (SM), FFP2/N95, and exhalation valved FFP2/N95, while the most common exercises were treadmill and cycle ergometer incremental tests, beyond outdoor running, resistance exercises and functional tests. Mask-wearing during exercise lead to increased overall discomfort (SMD: 0.87; 95%CI 0.25 to 1.5; p=0.01; I²=0%), dyspnea (SMD: 0.40; 95%CI 0.09 to 0.71; p=0.01; I²=68%), and perceived exertion (SMD: 0.38; 95%CI 0.18 to 0.58; p<0.001; I²=46%); decreases on the TTE (SMD: -0.29; 95%CI -0.10 to -0.48; p<0.001; I²=0%); without effects on POMAX and walking/running distance traveled (p>0.05). Conclusion: Face mask wearing during exercise increases discomfort (large effect), dyspnea (moderate effect), and perceived exertion (small effect), and reduces the TTE (small effect), without effects on cycle ergometer POMAX and distance traveled in walking and running functional tests. However, some aspects may be dependent on the face mask type, such as dyspnea and perceived exertion.